Biomarker profile in stable Fontan patients. (15th April 2020) - Saraf, Anita; De Staercke, Christine; Everitt, Ian; Haouzi, Alice; Ko, Yi-An; Jennings, Staci; Kim, Jonathan H.; Rodriguez, Fred H.; Kalogeropoulos, Andreas P.; Quyyumi, Arshed; Book, Wendy
Abstract: Background: As the population of adults with congenital heart disease (CHD) grows, cardiologists continue to encounter patients with complex anatomies that challenge the standard treatment of care. Single ventricle Fontan palliated patients are the most complex within CHD, with a high morbidity and mortality burden. Factors driving this early demise are largely unknown. Methods and results: We analyzed biomarker expression in 44 stable Fontan outpatients (29.2 ± 10.7 years, 68.2% female) seen in the outpatient Emory Adult Congenital Heart Center and compared them to 32 age, gender and race matched controls. In comparison to controls, Fontan patients had elevated levels of multiple cytokines within the inflammatory pathway including Tumor Necrosis Factor-α (TNF-α) ( p  < 0.001), Interleukin-6 (IL-6) ( p  < 0.011), Growth Derived Factor-15 (GDF-15) ( p  < 0.0001), β2-macroglobulin, ( p  = 0.0006), stem cell mobilization: Stromal Derived Factor-1∝ (SDF-1α) ( p  = 0.006), extracellular matrix turnover: Collagen IV ( p  < 0.0001), neurohormonal activation: Renin ( p  < 0.0001), renal dysfunction: Cystatin C ( p  < 0.0001) and Urokinase Receptor (uPAR) ( p  = 0.022), cardiac injury: Troponin-I ( p  < 0.0004) and metabolism: Adiponectin ( p  = 0.0037). Within 1 year of enrollment 50% of Fontan patients had hospitalizations, arrhythmias or worsening hepatic function. GDF-15 was significantly increased in Fontan patients with clinical events ( p  < 0.0001). In addition, GDF-15 moderately correlated with longer duration of Fontan ( r  = 0.55, p  = 0.01) and was elevated in atriopulmonary (AP) Fontan circulation. Finally, in a multivariate model, VEGF-D and Collagen IV levels were found to be associated with a change in MELDXI, a marker of liver dysfunction. Conclusion: Multiple clinical and molecular biomarkers are upregulated in Fontan patients, suggesting a state of chronic systemic dysregulation. Highlights: Fontan patients are the most complex within a fast-growing population of adults with CHD. Traditional diagnostic tests are not predictive of short-term outcomes in Fontan patients. Our study shows that multiple systemic biomarkers are dysregulated in stable Fontan patients. GDF-15 correlates with increased clinical events within 1 year in stable Fontan patients. VEGF-D and collagen IV levels are elevated in Fontan patients with worsening hepatic dysfunction.